2021
DOI: 10.3390/antibiotics10101144
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Related Adverse Drug Reactions in Patients Treated on the Dermatology Ward of Medical University of Gdańsk

Abstract: Adverse drug reactions (ADRs) are unexpected reactions to a medication administered in a correct way at a standard dose. Drug-induced skin reactions account for 60–70% of all ADRs. The aim of the study is to determine the prevalence of antibiotic-related dermatological ADR in patients treated in the department of Dermatology, Venerology and Allergology of the University Clinical Center in Gdańsk, Poland, in the years 2004–2021. A retrospective analysis of patients’ medical files was conducted in order to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Currently, clinicians are still treating bacteria or fungi causing infections with antibiotics; 1,2 however, antibiotics have many serious adverse effects. 3,4 Antibiotics are exerting antibacterial efficacy, while pathogenic bacteria are constantly adapting to them, resulting in drug resistance. Coupled with the misuse of drugs, the failure of existing antibiotics leads to the subsequent creation of some superbugs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, clinicians are still treating bacteria or fungi causing infections with antibiotics; 1,2 however, antibiotics have many serious adverse effects. 3,4 Antibiotics are exerting antibacterial efficacy, while pathogenic bacteria are constantly adapting to them, resulting in drug resistance. Coupled with the misuse of drugs, the failure of existing antibiotics leads to the subsequent creation of some superbugs.…”
Section: Introductionmentioning
confidence: 99%
“…Among all types of ADRs, the cutaneous adverse drug reactions (cADRs) are the commonest and may represent up to 30% to 60% of all ADRs [12,3]. Sokolewicz et al, (2021) reported even more higher rates (60-70%) [14]. Incidences of cADRs vary globally, being 1-3% in the developed countries and 2-5% in developing countries [11,15,16].…”
Section: Background and Introductionmentioning
confidence: 99%
“…Among all types of ADRs, the cutaneous adverse drug reactions (cADRs) are the commonest and may represent up to 30% to 60% of all ADRs [12,3]. Sokolewicz et al, (2021) reported even more higher rates (60-70%) [14]. Incidences of cADRs vary globally, being 1-3% in the developed countries and 2-5% in developing countries [11,15,16].…”
Section: Background and Introductionmentioning
confidence: 99%